Kepuasan Kerja sebagai Variabel Pemediasi Pengaruh Motivasi Kerja terhadap Kinerja pada PT INKOASKU Jawa Barat - Rahmawati Riantisari; Anna Partina (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
The purpose of this study is to analyze the performance of employees in the production department at PT. INKOASKU, Karawang, West Java. This study analyzes the effect of motivation on employee performance. This study using the variable job satisfaction as an intervening variable. The population in this study are 80 production employees of PT INKOASKU Karawang, West Java. The sampling technique used is the model non- probability sampling by census method. This study uses a questionnaire data collection method that is distributed to all employees of the production section, amounting to 80 people. The result was that 68 questioners were filled by the productions employees of PT INKOASKU Karawang, West Java, the respondent rate was 85%. The analytical tool used is Hierarchical Regression Analysis. The result is that work motivation does not affect employee performance, work motivation has a significant positive effect on employee performance, job satisfaction has a significant positive effect on employee performance and job satisfaction acts as a mediating variable between work motivation and employee performance.